Differentiation of embryonic stem cells is induced by GATA factors - Fujikura, Junji (Cold Spring Harbor Laboratory Press, 2002)
Extraembryonic endoderm (ExE) is differentiated from the inner cell mass of the late blastocyst-stage embryo to form visceral and parietal endoderm, both of which have an important role in early embryogenesis. The essential roles of Gata-6 and Gata-4 on differentiation of visceral endoderm have been identified by analyses of knockout mice. Here we report that forced expression of either Gata-6 or Gata-4 in embryonic stem (ES) cells is sufficient to induce the proper differentiation program towards ExE. We believe that this is the first report of a physiological differentiation event induced by the ectopic expression of a transcription factor in ES cells.